2021
DOI: 10.33448/rsd-v10i12.20618
|View full text |Cite
|
Sign up to set email alerts
|

Alfa-bisabolol: uma revisão de propriedades bioativas antiflogísticas

Abstract: O presente trabalho objetivou identificar e sistematizar obras científicas que atribuem ao alfa-bisabolol (BISA) atividades antiflogísticas. Trata-se de uma revisão bibliográfica, cuja seleção dos artigos foi realizada nas bases de dados PubMed, Web of Science e Science Direct. Para fins de coleta de dados foi utilizado as diretrizes PRISMA e o método de Bardin. A estratégia de pesquisa identificou 257 artigos que após triagem foram elegíveis para a revisão 37. Os critérios de inclusão definidos foram: artigos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 64 publications
0
2
0
Order By: Relevance
“…The sunflower [ 28 , 29 ] and rosehip [ 30 ] oil concentrations were selected based on studies showing their biological activity in the concentrations used. Alpha-bisabolol was added to the formulation in adequate amounts to exert its antioxidant action [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…The sunflower [ 28 , 29 ] and rosehip [ 30 ] oil concentrations were selected based on studies showing their biological activity in the concentrations used. Alpha-bisabolol was added to the formulation in adequate amounts to exert its antioxidant action [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…Research conducted in rats has demonstrated the analgesic and anti-inflammatory effects of the essential oil from the leaves of Eremanthus erythropappus (Sousa et al, 2008). Most of the reviewed articles have shown the effectiveness of α-bisabolol in inflammatory, painful, and edematous conditions, as well as in various types of wounds, including chronic inflammations, surgical wounds, and burns, demonstrating proven activity in various diseases, such as calming, anti-allergic, antibacterial, antiinflammatory, antineoplastic, antioxidant, hepatoprotective, and analgesic effects, among others (Amaral et al, 2021). Furthermore, the potential use of candeia oil in biological dressings has been demonstrated, evidencing the slow release of α-bisabolol inside the wound Moraes, 2016).…”
Section: Candeia (Eremanthus Erythropappus) Oilmentioning
confidence: 99%